Conceptualizing deviance: a cross-cultural social network approach to comparing relational and attribute data - Bright, Candace Forbes (Lexington Books, 2016)
Introduction -- Deviant behavior and social network analysis -- Data collection -- Approach one: deviance across cultures -- Approach two: social influence in approval of deviant behavior -- Approach three: birds of a feather approve of deviant behavior together -- Conclusion